Vivendo e aprendendo no ambiente hospitalar: Percepções de crianças sobre a doença - Monteiro, Luciana Fernanda Lucena Mendes (2007)
This study focuses on the child within the hospital environment. Its purpose is to describe children s perceptions of their illness and time in hospital and to identify their main hardships during treatment. This study has a qualitative nature and is theoretically and methodologically supported by the creative and sensitive method developed by Cabral (1998), studies by Piaget, Vygotsky and Wallon on child development, and studies conducted by Pinto (2005), Collet (2004), Chiattone (2003), Silva (2002), Lima et.al (1999) on in-patient children. For this study, 13 children between the ages of 7 and 12 at a public hospital institution specialized in child care in the city of Natal, Rio Grande do Norte, were interviewed. As a criterion for taking part in this study the children would have to have been in hospital for over three days and be fully capable of physically and emotionally interacting with the researcher at the time the interview took place. Analysis drew on the study of the empirical material made up of interviews and a field diary where notes had been entered for the children s reactions, expressions and gestures. Results show that there is some understanding, on the part of these children, of their illness, with their parents as the main informants. They accept being in hospital because they need treatment, but they realize that life becomes different especially on account of the constraints resulting from the illness and the hospital itself. The main hardships during treatment are: lack of recreational activities in the evenings and on the weekends within the hospital environment; absence of family members, especially brothers and sisters; and lack of explanation on the part of health professionals regarding some procedures as these are being carried out. Our conclusion is that children perceive illness and the hospital environment as something that changes the rhythm of their lives bringing on them perturbations, fears and anxieties. Hence, we suggest that professionals working with in-patient children should be especially prepared to deal with these children and their parents, aiming at bringing down fears and anguishes, clear their doubts and, in addition, advise the parents in respect of their children s treatment while in hospital and after hospital discharge. The hospital environment should also be cheerful and colorful and have a toy room under the coordination of persons especially prepared for that purpose